1988
DOI: 10.1111/j.1439-0450.1988.tb00560.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Type of Fimbriae on Salmonella typhimurium

Abstract: Thin (3 nm) flexible fimbriae are shown which are mannose-resistent in hemagglutination. They were found on 35 strains of Salmonella typhimurium inclusively variatio Copenhagen, specific for pigeons, which were isolated from clinical cases of Salmonellosis. These thin fimbriae as lectins are of interest for adhesion to the intestine. Unlike the type 1 fimbriae (7nm) they don't need mannose as receptor on the cell membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 5 publications
1
30
0
Order By: Relevance
“…The biosynthesis of type 1 fimbriae is mediated by the fimAICDHF operon of serotype Typhimurium (3,14,23). A distinct fimbrial type, termed thin curled fimbriae, was subsequently described by electron microscopic observation of the surfaces of serotype Typhimurium cells grown on agar plates (10). N-terminal sequencing of the major subunit of thin curled fimbriae, termed AgfA (CsgA), identified this structure as being orthologous to the thin aggregative fimbriae of S. enterica serotype Enteritidis and the curly fimbriae of Escherichia coli (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biosynthesis of type 1 fimbriae is mediated by the fimAICDHF operon of serotype Typhimurium (3,14,23). A distinct fimbrial type, termed thin curled fimbriae, was subsequently described by electron microscopic observation of the surfaces of serotype Typhimurium cells grown on agar plates (10). N-terminal sequencing of the major subunit of thin curled fimbriae, termed AgfA (CsgA), identified this structure as being orthologous to the thin aggregative fimbriae of S. enterica serotype Enteritidis and the curly fimbriae of Escherichia coli (26).…”
Section: Discussionmentioning
confidence: 99%
“…Whole-genome sequencing has revealed the presence of 13 operons containing open reading frames with homology to fimbrial gene sequences in the serotype Typhimurium genome (15). Only two of these operons, fim and agf (csg), have been shown by electron microscopy to mediate the expression of fimbrial filaments on the surfaces of serotype Typhimurium cells grown in broth or on agar plates, respectively (6,10). An expression analysis of putative major fimbrial subunits from 11 serotype Typhimurium fimbrial operons by flow cytometry showed that only FimA is detectable on the bacterial surface after growth of the organism in Luria-Bertani (LB) broth (11).…”
mentioning
confidence: 99%
“…Only two of the encoded adhesins are well expressed in vitro, including type 1 fimbriae encoded by the fim operon (4,6) and thin curled fimbriae (also known as thin aggregative fimbriae or curli) encoded by the csg (agf) gene cluster (9,29,33), but the expression of both adhesins is also subject to regulation. The lack of in vitro expression of the remaining adhesins has in many cases prevented their identification by methods other than sequence analysis.…”
mentioning
confidence: 99%
“…The S. Typhimurium LT2 genome encodes 13 adhesin gene clusters (14,54), several of which have been analyzed functionally in the past. These include type I fimbriae (Fim) (8,12,44), plasmid-encoded fimbriae (Pef) (2,19,50), long polar fimbriae (Lpf) (1), thin aggregative fimbriae (Agf) (23,55,67), the adhesin ShdA (39), and also Salmonella pathogenicity island 4 (SPI-4), encoding the YadA-like adhesin SiiE (21). SiiE enhances T1-mediated invasion into polarized epithelial cells but not into fibroblasts and other nonpolarized cells (20).…”
mentioning
confidence: 99%